CORRELATION OF PERFUSION AND CONTRACTILITY OF LEFT VENTRICLE MYOCARDIUM ON GATED MYOCARDIAL PERFUSION SCINTIGRAPHY - Asghar, Asghar Hussain; Rizvi, Sadia; Shah, Shoab; Rauf, Muhammad; Khan, Ayub; Irfan, Javed (Journal of Ayub Medical College Abbottabad, 2007)
Background: Gated Single Photon Emission Computerized Tomography (SPECT) is a modality which is helpful in the detection of wall motion, thickening and ejection fraction of left ventricle. The purpose of this study was to correlate the ungated and gated SPECT in evaluation of left ventricle dysfunction. Method: It was a prospective study done at Institute of Radiotherapy and Nuclear Medicine (IRNUM), Peshawar, in2001/02. 76 patients (47 male and 29 female) with an average age of 52±11 years were inducted in this study. All patients underwent two days stress-rest Tc-99m MIBI (Methoxy Isobutyl Isonitrile) gated SPECT scan where 1110 MBq (30 mCi) was injected intravenously. Eight frames gating technique (variable fixed temporal resolution) of ECG was used to gate the cardiac cycle and whole acquisition was completed in 30 minutes. Results: This technique very well evaluated the perfusion as well as wall motion/thickening (W/M/T) status of left ventricle. Out of 76 scans, 30% were normal, 22% transmural infarct, 25% partial thickness infarct, and 22% reversible ischemia. By doing the 20 segmental analyses, total 1520 segments were analyzed that revealed good concordance of perfusion with W/M/T in 78% of segments while 22% segments showed poor concordance. Out of these 22%, 12% were having more wall motion abnormalities than that of perfusion, while in 10%, it was vise versa. Conclusion: Results of this study shows good correlation between gated and ungated SPECT for evaluation of left ventricle dysfunction (r = 0.73, p=0.01). Key Words:Tc-99m MIBI; Ischemic heart disease; Gated SPECT.